Analytical Method Validation and Determination of Pyridoxine, Nicotinamide, and Caffeine in Energy Drinks Using Thin Layer Chromatography-Densitometry - Florentinus Dika Octa Riswanto; RR. Endang Lukitaningsih; Sudibyo Martono (Universitas Gadjah Mada, 2015)
Food supplement which contains vitamins and stimulants such as caffeine were classified as energy drink. TLC-densitometry method was chosen to determine the pyridoxine, nicotinamide, and caffeine in the energy drink sample. TLC plates of silica gel 60 F254 was used as the stationary phase and methanol : ethyl acetate : ammonia 25% (134:77:10) was used as the mobile phase. The correlation coefficient for each pyridoxine, nicotinamide, and caffeine were 0.9982, 0.9997, and 0.9966, respectively. Detection and quantitation limits of from the three analytes were 4.05 and 13.51 µg/mL; 13.15 and 43.83 µg/mL; 5.43 and 18.11 µg/mL, respectively. The recovery of pyridoxine, nicotinamide, and caffeine were within the required limit range of 95-105%. The percent of RSD were below the limit value of 5.7% for caffeine and nicotinamide and 8% for pyridoxine. The content amount of pyridoxine in the sample 1 and 2 were 33.59 ± 0.981 and 30.29 ± 2.061 µg/mL, respectively. The content amount of nicotinamide in the sample 1 and 2 were 106.53 ± 3.521 and 98.20 ± 3.648 µg/mL, respectively. The content amount of caffeine in the sample 1 and 2 were 249.50 ± 5.080 and 252.80 ± 2.640 µg/mL, respectively. Robustness test results showed that the most optimal method conditions should be applied for the analysis.